Chaperone Like Attributes of Biogenic Fluorescent Gold Nanoparticles: Potential to Alleviate Toxicity Induced by Intermediate State Fibrils Against Neuroblastoma Cells - Mujeeb, Anzar Abdul; Alam, Khan Farheen Badre; Alshameri, Ansam Wadia Faid; Jamal, Fauzia; Farheen, Saba; Kashif, Mohd; Ahmed, Anees; Ghazi, Irfan Ahmad; Owais, Mohammad (Frontiers in Chemistry, 2019)
In general, neurodegenerative disorders have great deal of correlation with the misfolded as well as aggregated forms of protein-based macromolecules. Among various species formed during aggregation process, protein oligomers have been classified as most toxic entities against several types of living cells. A series of chemicals have been developed to inhibit protein aggregation as a measure to regulate neurodegenerative diseases. Recently, various types of nanoparticles have also been reported as potent inhibitors of protein aggregation. In the present study, we synthesised fluorescent gold nanoparticles (B-AuNPs) employing Olax scandens leaf extract. Next, we executed an in vitro study to elucidate the effect of as-synthesized B-AuNPs on the aggregation behaviour of the ovalbumin (OVA), a model protein. We performed extensive study to elucidate anti-amyloidogenic properties of nano-sized entities and established that small sized B-AuNPs manifest chaperone potential against protein aggregation. Further, we exploited as-synthesised B-AuNPs in prevention of protein aggregation mediated toxicity to neuroblastoma cells.